Fabrication of BP2T functionalized graphene via non-covalent π–π stacking interactions for enhanced ammonia detection. Issue 57 (8th November 2021) - Li, Hu; Duan, Tianbo; Sher, Omer; Han, Yuanyuan; Papadakis, Raffaello; Grigoriev, Anton; Ahuja, Rajeev; Leifer, Klaus
Abstract : Non-covalent functionalization of graphene has been achieved by employing π–π stacking interactions, and it is promising for ammonia detection with greatly enhanced sensitivity. Abstract : Graphene has stimulated great enthusiasm in a variety of fields, while its chemically inert surface still remains challenging for functionalization towards various applications. Herein, we report an approach to fabricate non-covalently functionalized graphene by employing π–π stacking interactions, which has potentialities for enhanced ammonia detection. 5, 5′-Di(4-biphenylyl)-2, 2′-bithiophene (BP2T) molecules are used in our work for the non-covalent functionalization through strong π–π interactions of aromatic structures with graphene, and systematic investigations by employing various spectroscopic and microscopic characterization methods confirm the successful non-covalent attachment of the BP2T on the top of graphene. From our gas sensing experiments, the BP2T functionalized graphene is promising for ammonia sensing with a 3-fold higher sensitivity comparing to that of the pristine graphene, which is mainly attributed to the enhanced binding energy between the ammonia and BP2T molecules derived by employing the Langmuir isotherm model. This work provides essential evidence of the π–π stacking interactions between graphene and aromatic molecules, and the reported approach also has the potential to be widely employed in a variety of graphene functionalizations for chemical detection.